Reposisi Peran Universitas dalam Memperkuat Ketahanan Ekonomi Masyarakat Desa Berbasis Ilmu Pengetahuan dan Teknologi: Perspektif Quadruple Helix - Asmara, Anugerah Yuka; Kusumawardhani, Dhian; Hidayati, Emi (Proceedings of Annual Conference on Community Engagement, 2022)
University has been main leverage to economics development in developed countries which is called as knowledge-based economy (KBE). In turn, developing countries are pursued to catch up develop countries through KBE. In Indonesia case, university carries up slogan “Tri Dharma Perguruan Tinggi” and entrepreneurial university. Consequently, university conducts all research and development (R&D) line from upstream (basic research) to downstream (R&D commercialization). It leads to university as the central position among business, government, and communities. This study uses quadruple helix concept by which university, business, government, and communities should have balanced role to make university’s role real, especially related to strengthening economics of rural people. Qualitative approach is used as research method to this study with optimizing data secondary sources. This study finding is that it is required reposition of university in doing its role among business, government, and society. It aims to clear university’s role and to show up its contribution to strengthen economics of society in rural areas.